Formas de viver, pensar e agir em saúde em uma comunidade pomerana do Espírito Santo - Rosario, Gustavo Felix do (2019)
It is a qualitative study inspired by the cartographic aproach and having as theoretical reference the institutionalism. It aims to understand the health experience, in particular oral health in a Pomeranian community placed in a munipality of Domingos Martins / Espírito Santo. The study scenerio was Tijuco Preto - that is part of Ponto Alto district. Eleven edentulous subjects from that locality were selected according to the Health Center’s employees criterion indication. The material production instruments were narrative interviews and field diary, obtained from the observation throughout the process of FieldWork. The interviews were based on a generative question, had have an average duration of forty-five minutes each and were mostly individual, at the time and place defined by the studied subjects. Those interviews were recorded and later transcribed, followed by the notes registraded on the field diary, the accurate reading of all the material, seeking meaning to the knowlegde construction with the subjects through cartographic aproach . The study evidenced that there was in the past an early dental loss experienced by the subjects which participated in the research, however, it showed a movement of change in the community that has transformed their customs.